2017
DOI: 10.18632/oncotarget.19283
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly activated Cox-2 and Wnt signaling interact to maintain cancer stem cells in glioblastoma

Abstract: Glioblastoma recurrence after aggressive therapy typically occurs within six months, and patients inevitably succumb to their disease. Tumor recurrence is driven by a subpopulation of cancer stem cells in glioblastoma (glioblastoma stem-like cells, GSCs), which exhibit resistance to cytotoxic therapies, compared to their non-stem-cell counterparts. Here, we show that the Cox-2 and Wnt signaling pathways are aberrantly activated in GSCs and interact to maintain the cancer stem cell identity. Cox-2 stimulates GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 52 publications
1
44
0
1
Order By: Relevance
“…Микроокружение опухоли играет важную роль в канцерогенезе глиобластомы, влияя на фенотип СКГ. Было показано, что COX2 (циклооксигеназа 2) ассоциированный сигнальный путь и повышенный синтез PGE2 (простагландин E2) приводят к увеличению пролиферации и самообновления СКГ и НСК in vitro посредством активации Wnt / β-катенин-каскада, в то время как ингибирование COX2 индуцировало дифференцировку и потерю фенотипа СКГ [61].…”
Section: обзорные статьиunclassified
“…Микроокружение опухоли играет важную роль в канцерогенезе глиобластомы, влияя на фенотип СКГ. Было показано, что COX2 (циклооксигеназа 2) ассоциированный сигнальный путь и повышенный синтез PGE2 (простагландин E2) приводят к увеличению пролиферации и самообновления СКГ и НСК in vitro посредством активации Wnt / β-катенин-каскада, в то время как ингибирование COX2 индуцировало дифференцировку и потерю фенотипа СКГ [61].…”
Section: обзорные статьиunclassified
“…Increasing levels of COX-2 expression and prostaglandin E2 are associated with cell proliferation, invasion, and angiogenesis, and apoptosis inhibition, and the COX-2 expression level is positively correlated with glioma grade [177]. Furthermore, an aberrant positive feedback interaction between the COX-2/PGE2 and WNT pathways stimulates the self-renewal and proliferation of GSCs [178]. WNT signaling underlies GSC identity directly through COXindependent WNT signaling, and indirectly through COX/ PGE2-dependent WNT signaling [178].…”
Section: Interactions Between B-catenin Signaling and Ppar-c Agonistsmentioning
confidence: 99%
“…Furthermore, an aberrant positive feedback interaction between the COX-2/PGE2 and WNT pathways stimulates the self-renewal and proliferation of GSCs [178]. WNT signaling underlies GSC identity directly through COXindependent WNT signaling, and indirectly through COX/ PGE2-dependent WNT signaling [178].…”
Section: Interactions Between B-catenin Signaling and Ppar-c Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced expression of COX-2 protein has been correlated with many aggressive aspects of the disease, such as rate of GBM cell proliferation [13], histopathological grade of glioma [14,15], and poor prognosis and survival [16][17][18][19]. Furthermore, evidence has been reported that the COX-2 pathway, through the stimulation of the GSC self-renewal and proliferation, could contribute to chemo-and radioresistance [20][21][22]. Hence, COX-2 has been proposed as a strong predictor of poor survival and aggressiveness [12,18] as well as its targeting with specific COX-2 inhibitors is emerging as a potential anti-glioma strategy [12,14,23,24].…”
Section: Introductionmentioning
confidence: 99%